Pencetakan Mushaf Al-Qur’an di Indonesia - Akbar, Ali (Lajnah Pentashihan Mushaf Al-Qur'an, 2011)
This article outlines the development of the printing of the QurÃ¢â‚¬â„¢anÃ‚Â inÃ‚Â Indonesia from its advent in the middle of 19th century to the present.Ã‚Â It also traces the influence of printed QurÃ¢â‚¬â„¢ans fromÃ‚Â India andÃ‚Â Turkey onÃ‚Â the early period of QurÃ¢â‚¬â„¢anic printing inÃ‚Â Indonesia, and gives brief descriptions of some publishers of the QurÃ¢â‚¬â„¢an throughout the period in question. The last section analyses recent creative developments in the QurÃ¢â‚¬â„¢an publishing industry inÃ‚Â Indonesia.